Assessment of Stand-Alone Residential Solar Photovoltaic Application in Sub-Saharan Africa: A Case Study of Gambia - Kanteh Sakiliba, Sambu; Sani Hassan, Abubakar; Wu, Jianzhong; Saja Sanneh, Edward; Ademi, Sul (Journal of Renewable Energy, 2015)
The focus of this paper is the design and implementation of solar PV deployment option, which is economical and easy to maintain for remote locations in less developed countries in Sub-Saharan Africa. The feasibility of stand-alone solar PV systems as a solution to the unstable electricity supply and as an alternative to the conventional resource, “diesel generators,” is presented. Moreover, a design of a system is carried out, such that the electrical demand and site meteorological data of a typical household in the capital, Banjul, is simulated. Likewise, the life cycle cost analysis to assess the economic viability of the system, along with the solar home performance, is also presented. Such system will be beneficial to the inhabitants of Gambia by ensuring savings in fuel costs and by reducing carbon emissions produced by generators. The selection of appropriate-sized components is crucial, as they affect the lifetime, reliability, and initial costs. The design presented in this study represents a solution for domestic houses to adopt the system according to the location and environment, in order to meet electricity demand.